Do patients need additional coverage for chronic ailments? Insights from hospital data - Aswin Sugunan; K Rajasekharan Pillai; Brayal D'souza; Anice George (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Eliminating financial barriers and improving healthcare accessibility pertain to be key elements of the United Nation's sustainable development goals. These have directed health policymakers to advocate private health insurance as a health promotion strategy to enable patients to obtain absolute and affordable medical care when needed. Against this backdrop, the current study investigates the coverage trend and financial risk-protective nature of private health insurance plans. MATERIALS AND METHOD: We examined 12 months' hospital billing data of private health insurance holders with cancer, cardiac, neurological, and renal diseases. The billing and insurance claim data of 5002 patients were extracted from the billing section of a tertiary care teaching hospital located in southern India from April 2022 through March 2023. Five per cent of patients from each disease condition were selected through proportionate random sampling for analysis (n = 250). The cost incurred and reimbursement trend under various cost heads were investigated by examining the cost incurred by the patient during the hospitalization and comparing it with the amount reimbursed by the insurance company. RESULTS: The scrutiny exhibits that private health insurance fails to provide comprehensive coverage, resulting in under-insurance among subscribers. Reimbursement received for each cost category is also discussed. To the best of our knowledge, this is the first study that has used institutional data instead of large survey data or patient data. CONCLUSION: The research concludes by soliciting policymakers, healthcare providers, and insurers to develop strategies to enhance the affordability and accessibility of healthcare to promote health and wellness.